2005
DOI: 10.1107/s0108768105017258
|View full text |Cite
|
Sign up to set email alerts
|

A variable-temperature study of a phase transition in barbituric acid dihydrate

Abstract: The crystal structure of barbituric acid dihydrate (C4H4N2O3*2H2O) has twice been reported as orthorhombic, space group Pnma, with all atoms (except for CH(2) H atoms) lying on the mirror plane [Al-Karaghouli et al. (1977). Acta Cryst. B33, 1655-1660; Jeffrey et al. (1961). Acta Cryst. 14, 881-887]. The present study has found that at low temperatures, below 200 K, the crystal structure is no longer orthorhombic but is non-merohedrally twinned monoclinic, space group P2(1)/n. This phase is stable down to 100 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…8 Polymorph transitions in molecular solids are typically viewed as discontinuous, 9,10 exhibiting clear and immediate transformations between forms, yet continuous transformations have also been reported. 11 A possible explanation for an apparent continuous phase transformation involves the ability of two (or more) polymorphs to exist simultaneously (concomitant polymorphism), which could manifest itself experimentally as a continuous redistribution of the relative populations of the two polymorphs involved. While single-crystal X-ray diffraction (SCXRD) is the most common method for determining solid-state structures, it is difficult to characterize the packing energies or thermodynamic stabilities of materials with it.…”
mentioning
confidence: 99%
“…8 Polymorph transitions in molecular solids are typically viewed as discontinuous, 9,10 exhibiting clear and immediate transformations between forms, yet continuous transformations have also been reported. 11 A possible explanation for an apparent continuous phase transformation involves the ability of two (or more) polymorphs to exist simultaneously (concomitant polymorphism), which could manifest itself experimentally as a continuous redistribution of the relative populations of the two polymorphs involved. While single-crystal X-ray diffraction (SCXRD) is the most common method for determining solid-state structures, it is difficult to characterize the packing energies or thermodynamic stabilities of materials with it.…”
mentioning
confidence: 99%
“…The original X-ray [10] and neutron [11] single-crystal diffraction studies of barbituric acid dihydrate BAH•2H2O at room temperature locate all the ring atoms on a crystallographic mirror plane in the orthorhombic space group Pnma, so the ring is necessarily exactly planar. However, a redetermination at 150 K indicated a twinned structure in the monoclinic space group P21/n, in which the mirror plane is absent; [12] the unit cell parameters are similar and the lower-symmetry lowtemperature structure is clearly the consequence of a phase transition on cooling. We carried out a detailed examination of this structural change with data collections at a range of temperatures, and concluded that the ring becomes non-planar on cooling through the transition point, with a dihedral angle reaching 8.2 ° at 100 K. The water molecules in this structure, coplanar with the acid molecule in the orthorhombic room-temperature form, are displaced significantly out of this plane in the low-temperature form.…”
Section: Conformation Of the Barbituric Acid Six-membered Ringmentioning
confidence: 99%
“…Apart from the alkali metal halide ionic cocrystals mentioned above and two similar calcium halide ionic cocrystals, [5,6] a search of the Cambridge Structural Database (version 5.39 with two updates, February 2018) finds only 21 structures together with polymorphs of BAH itself [7][8][9] and its dihydrate. [10][11][12] These include mainly cocrystals with various organic partners, [13][14][15][16][17][18][19][20][21][22][23][24] a few structures containing both BAH and its anion BAtogether with an organic or alkali metal cation, [25][26][27] and an ionic cocrystal with the potassium salt of [Pt2I6] 2− . [28] We have undertaken various structural studies of barbituric acid and related heterocyclic compounds such as violuric and cyanuric acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2005 literature also contained a number of additional reports that summarized investigations of the phase transitions among polymorphs and solvatomorphs of various organic compounds, and the thrust of these159–166 have been summarized in Table 3.…”
Section: Phase Transformations Of Polymorphs and Solvatomorphsmentioning
confidence: 99%